Bukan Sekadar Utara dan Selatan: Kajian Kritis terhadap Binaritas dalam Wacana Global North-South: Beyond North and South: A Critical Study of Binarism in Global North-South Discourse - Andrew Elnathan; Aswin Ariyanto Azis (Emik : Jurnal Ilmiah Ilmu-Ilmu Sosial, 2026)
The study of international development politics initially had a status quo which was studied by categorizing countries between the North (“Global North”) and the South (“Global South”). Therefore, previous studies have focused more on using the concepts of Global North and Global South as a framework to describe global development inequality.   This article critiques the hierarchical ontology and epistemology prevalent in Global North and Global South studies in international development, which have been widely adopted but fail to capture the complexity of contemporary global relations adequately. This research employs a qualitative, literature-based methodology, drawing on critical scholarship in postcolonialism, development studies, and international relations. Through interpretive analysis and literature review, the study deconstructs dominant narratives surrounding the North–South divide and evaluates their theoretical and empirical limitations.   The findings reveal several key contributions to socio-political North–South studies. First, the article demonstrates that the binary classification fails to account for internal heterogeneity and dynamic transformations within states, as evidenced by cases such as Cina, which challenges conventional developmental hierarchies. Second, the study introduces a deconstructive framework inspired by Derridean thought, showing that the North–South dichotomy is not a neutral analytical tool, but a politically constructed discourse embedded with epistemic bias. Third, the incorporation of postcolonial perspectives, such as the “upside-down world map” and bottom-up approaches, offers a novel way to reconceptualize global relations beyond rigid geographical determinism. These findings advance the field by proposing that development should be understood as a multidimensional and context-specific process shaped by historical, sociological, and transnational factors, rather than fixed binary categories. Ultimately, this article contributes to the growing urgencies for a more reflexive, pluralistic, and decolonized framework in global development and international relations scholarship.